(untitled) (Universal International Scientific Journal, 2026)
In the course of personality development, the factors affecting the formation of consciousness, character, emotional state and social adaptation in the stages of childhood, adolescence, youth and adulthood are highlighted. The article justifies the importance of considering age-related psychological characteristics in the process of education, in the design of educational work and social environment. The results of the research are explained to strengthen the individual approach in working with the young generation, improve pedagogical strategies and effectively organize psychological support mechanisms.